Answer:
Negetive
Step-by-step explanation:
It helps to re-write.
-6 + -6 is the same as -6 -6
-6 + -6 = - 12
It would be different if these were multiplied together, but AS WRITTEN, they are subtracted. If it was (-6)(-6) or -6(-6) that would indicate multiplication as well.
The answer is negative.
Answer:
<em>a) 15 b) 6 c) -3</em>
Step-by-step explanation:
x - y = 3
a) 5 (x - y) = 5 (3) = 15
b) 2x - 2y = 2 (x - y) = 2 (3) = 6
c) y - x = -1 (x - y) = -1 (3) = -3
Hey there!
⇒ Use the vertex as the middle letter, and the point from each side (<ABC or <CBA)
⇒ Use the vertex only (<B)
⇒ Use a number (<1)
- Classify angles according to their measure.
⇒ Acute angle: less than 90°
⇒ Right angle: exactly 90°
⇒ Obtuse angle: between 90° and 180°
⇒ Straight angle: exactly 180°
Thank you,
Eddie
See the attachment for a visual!
The answer is A because of base times height
The property that is applied in
is addition property of equality
Given :
![If \; 7m=35, then \; 7m+4=35+4](https://tex.z-dn.net/?f=If%20%5C%3B%207m%3D35%2C%20then%20%5C%3B%207m%2B4%3D35%2B4)
From the above equation we can see that 4 is added at the both sides of the equation .
we can add same number at the both sides of the equation to balance the equation . That is called as addition property of equality
Here , 4 is added on both sides of the equality to balance the equation .
So , addition property of equality is applied .
Learn more : brainly.com/question/24214650